International and Domestic Law Dimensions of Climate Justice for Arctic Indigenous Peoples - Kronk Warner, Elizabeth; Abate, Randall (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2013)
The Arctic region is in crisis from the effects of climate change. The impacts of climate change pose a particular threat to Arctic indigenous communities. Because of the disproportionate impacts of climate change, these indigenous communities are environmental justice communities. Part I of this article discusses how indigenous nations are environmental justice communities and discusses the unique factors that may apply to environmental justice claims arising in Indian country. The article then presents two case studies to explore how, if at all, these concepts have been previously applied to environmental justice claims brought by various Arctic indigenous communities. Part II addresses the Inuit Circumpolar Conference’s petition to the Inter-American Commission on Human Rights. Part III considers the Native Village of Kivalina’s lawsuit against numerous private emitters of greenhouse gases. These case studies underscore the failure of international and domestic forums’ consideration of the special situation of Arctic indigenous peoples as environmental justice communities.